2020
DOI: 10.1186/s12913-020-05928-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials and drug cost savings for Italian health service

Abstract: Background The cost of anticancer drugs is constantly growing. The aim of this study was determine the impact in terms of cost reduction for anticancer drug in the Italian Health Service due to patient participation in clinical trials. Methods We evaluated the cost of drugs administered to patients treated in clinical trials at the National Cancer Institute of Naples in a four-week time period. Patients with a diagnosis of different cancers were considered, including adjuvant therapy and treatment for advance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…These findings cannot be fully compared with the economic impact of a CT. If Italian studies on CT avoided costs are considered, regarding only medicines [ 31 , 32 ] and diagnostic procedures [ 30 ], the mean savings per patient treated are higher in our findings. This is mainly caused by the higher cost of the hypothetical SoC used in clinical practice.…”
Section: Discussionmentioning
confidence: 54%
“…These findings cannot be fully compared with the economic impact of a CT. If Italian studies on CT avoided costs are considered, regarding only medicines [ 31 , 32 ] and diagnostic procedures [ 30 ], the mean savings per patient treated are higher in our findings. This is mainly caused by the higher cost of the hypothetical SoC used in clinical practice.…”
Section: Discussionmentioning
confidence: 54%
“…To estimate the DCA, we used the price of the best standard of care, resulting in ~5.1 million euros (Table 1). Other DCA estimations performed in a single institution have shown similar saving percentages for the hospital or institution budget 11,12 . Thus, supporting the idea that the DCA from oncological clinical trials provides economic savings, and may help to sustain the national health system.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies have estimated the drug cost avoidance based on the price of investigational drugs, and when this price is not available, taking as a reference the price of a control drug or standard treatment ( 11 , 18 , 21 ). However, some other studies like ours have used the standard therapy as a comparator ( 10 , 12 , 16 ), which we believe provides a more comprehensive analysis since clinical trials with novel agents with price not available are not excluded, as observed in other studies ( 11 , 14 , 15 ). In fact, among all the active oncology clinical trials in our hospital, only the multi-tumor trials were excluded from the economic analysis since a suitable comparator was not found.…”
Section: Discussionmentioning
confidence: 97%